Utility of icobrain for brain volumetry in multiple sclerosis clinical practice - Nguyen, Ai-Lan; Sormani, Maria Pia; Horakova, Dana; Havrdova, Eva H; Barnett, Michael H; De Stefano, Nicola; Battaglini, Marco; Vaneckova, Manuela; Lui, Elaine; Gaillard, Frank; Desmond, Patricia M; Prime, Hayden; et al. (Multiple sclerosis and related disorders, 2024)
BACKGROUND: Few studies on multiple sclerosis (MS) have explored the variability of percentage brain volume change (PBVC) measurements obtained from different clinical MRIs. In a retrospective multicentre cohort study, we quantified the variability of annualised PBVC in clinical MRIs. METHODS: Clinical MRIs of relapse-onset MS patients were assessed by icobrain. Volumetric data were analysed on same-scanner and different-scanner MRI pairs if they passed quality control criteria. Alignment similarity between two images had to be comparable to same-scanner scan-rescan images. RESULTS: Of 6826 MRIs, 85 % had appropriate volumetric sequences and 4446 serial MRI pairs were analysed. 3334 (75 %) MRI pairs from 1207 patients met the inclusions. The PBVC of included MRI pairs showed variance of 0.78 % for same-scanner pairs and 0.80 % for different-scanner pairs. Further selection of included MRI pairs with the best variance resulted in 1885 (42 %) MRI pairs with PBVC variance of 0.34 %. Excluded MRI pairs with poor alignment similarity had variances of 2.97 % for same-scanner pairs and 20.79 % for different-scanner pairs. CONCLUSION: Icobrain should be utilised for PBVC determination only on selected MRIs with the best alignment similarity. Applying strict selection criteria for the included MRI pairs and longitudinal imaging on the same scanner remain mandatory to reduce PBVC variability.
Keywords: velikost orgánu; Volumetry; Male; retrospektivní studie; Icometrix; Organ Size; magnetická rezonanční tomografie; Multiple Sclerosis; Brain; Adult; dospělí; relabující-remitující roztroušená skleróza; mužské pohlaví; Multiple Sclerosis, Relapsing-Remitting; Real-world; lidé; ženské pohlaví; Humans; mozek; Retrospective Studies; Magnetic Resonance Imaging; Variability; Female; lidé středního věku; roztroušená skleróza; Middle Aged